Control Measures and Health Effects of Air Pollution: A Survey among Public Transportation Commuters in Malaysia - Wong, Li Ping; Alias, Haridah; Aghamohammadi, Nasrin; Ghadimi, Azadeh; Sulaiman, Nik Meriam Nik (MDPI, 2017)
This research aimed to investigate the control measures used by public transport commuters and their health (physical and psychological) effects due to exposure to air pollution during their daily commute and during haze days. From June to October 2016, 800 public transport commuters in urban cities in the heart of Selangor, Malaysia were interviewed. Of these, 25.4% reported sometimes/often wearing surgical masks during their daily commute, while 92.1% reported such use during haze days. The total control measure score against air pollutants during the daily commute was low; on a control measure scale of 0-18, the median rating during the daily commute was 8 (interquartile range (IQR) 6-10). During haze days, control measures improved slightly (median 14, IQR 12-16). Evidence of adverse health effects was present. During the daily commute under normal conditions, the three highest adverse health experiences were fatigue and weakness (35.5%), coughing (23.6%), and dizziness (18.2%). During haze days, the three highest adverse health experiences were headache (85%), coughing (84.8%), and breathing difficulties (84.5%). On a possible total adverse health (physical and psychological) experience scale of 0-22, the median rating during the daily commute was 1 (IQR 0-3). The median rating during haze days was intensified (median 11, IQR 9-13). Public transportation commuters should be encouraged to enhance various control measures against particulate air pollutants during their daily commute, particularly during haze days, to minimize the adverse health risks associated with air pollutants.